HARVESTING COST MODEL FOR SMALL TREES IN NATURAL STANDS IN THE INTERIOR NORTHWEST. - HARTSOUGH, BRUCE R. ; ZHANG, XIAOSHAN ; FIGHT, ROGER D.
REALISTIC LOGGING COST MODELS ARE NEEDED FOR LONG-TERM FOREST MANAGEMENT PLANNING. DATA FROM NUMEROUS PUBLISHED STUDIES WERW COMBINED TO ESTIMATE THE COSTS OF HARVESTING SMALL TREES IN NATURAL STANDS IN THE INTERIOR NORTHWEST OF NORTH AMERICA....
Sala de Colecciones abiertas
Inglés
R2290
FORE
Keywords: ADMINISTRACION FORESTAL; ECOSISTEMAS; APROVECHAMIENTO FORESTAL; Artículos de revista